Flexible, high-sensitive and multifunctional wearable sensor based on the dual bioinspired spinosum microstructure of carbon nanotube/carbon black-coated polydimethylsiloxane film. (15th February 2023) - Zhu, Hao; Jin, Zhelin; Bai, Hongyu; Cao, Jie; Dong, Xu; Zhong, Yan; Dai, Shengping; Cheng, Guanggui; Yuan, Ningyi; Ding, Jianning
Highlights: Inspired by human skin, a novel dual spinosum microstructured sensor was fabricated. The sensor demonstrated high pressure sensitivity and excellent cycle stability. Our sensor has excellent capabilities in temperature and texture roughness detection. Abstract: The bionic sensor imitates the function of biological perception of external stimuli, which have attracted tremendous attentions. However, it remains a great challenge to prepare wearable bioinspired sensor with highly sensitive at low pressure and with multifunctional sensory capabilities. Herein, inspired by the spinosum structure of human skin, a novel surface morphology with dual spinosum microstructure (DSM) sensor was constructed by using clay and sucrose double template method. Benefiting from the reconfigurable behavior of the DSM, the assembled piezoresistive sensor demonstrated high sensitivity (32.9 kPa −1 ), pressure detection limit of 11 Pa, short response time (＜400 ms), and excellent stability (loading/unloading test of 3000 cycles). In practical application, the sensor showed excellent sensing performance in differentiating tiny stress changes and monitoring human motion in all directions, such as respiration, pulse, bending motions and gestures. Additionally, the novel sensor can detect environmental temperatures and recognize textures, which showed promising applications in intelligent electronic skins and human health monitoring.